Enhanced performance of lithium–sulfur batteries based on single-sided chemical tailoring, and organosiloxane grafted PP separator. Issue 31 (12th May 2020) - Zhou, Haifeng; Tang, Qunli; Xu, Qianer; Zhang, Yan; Huang, Cong; Xu, Yali; Hu, Aiping; Chen, Xiaohua
Abstract : Even after a decade of research and rapid development of lithium–sulfur (Li–S) batteries, the infamous shuttle effect of lithium polysulfide is still the major challenge hindering the commercialization of Li–S batteries. Abstract : Even after a decade of research and rapid development of lithium–sulfur (Li–S) batteries, the infamous shuttle effect of lithium polysulfide is still the major challenge hindering the commercialization of Li–S batteries. In order to further address this issue, a functionalized PP separator is obtained through selective single-sided chemical tailoring, and then organosiloxane fumigation grafting. During the charge–discharge process, the grafted functional groups can effectively block the transportation of the dissolved polysulfides through strong chemical anchoring, inhibit the shuttle effect and greatly enhance the cycle stability of the Li–S battery. Interestingly, the specially designed single-sided enlarged channel structure formed by chemical tailoring can well accommodate the deposition with intermediate polysulfides on the separator surface toward the cathode chamber, resulting in enhanced initial discharge capacity and rate performance. Compared to the battery assembled with PP, the Li–S battery employing the separator grafted with a 3-ureidopropyltrimethoxysilane (PP–O x − –U) displays better electrochemical performance. Even at 2C, it can still deliver a high capacity of 786 mA h g −1, and retain a capacity of 410 mA h g −1 with a low capacity fading of 0.095% per cycle over 500 cycles. This work provides a very promising and feasible strategy for the development of a special functionalization PP separator for Li–S batteries with high electrochemical performance.